Strategic Sales – Customer Portfolio Management - Murphy, John (2010)
This study investigates a proposition posed in the group project. While the group project demonstrated the importance of examining the approach to sales, this proposition looks at a specific segment of sales, customer portfolio management. There exists a theory put forward by Piercy and Lane in 2009 which looks at the array of customers that an organisation is about to target and states that attention should be given to the level of investment given to each one. On one end of the scale, some suppliers try to become strategically entrenched with a large buyer as they feel that the permanent nature of this relationship will lead to long term profits through developing the ability to sell large volumes, develop the relationship towards gaining a strong understanding of the particular value perceived by the customer and to protect the account by having the buyer rely on the infrastructure created between the two firms. Piercy and Lane purport the risks of such an approach in terms of the extended vulnerability that such a relationship presents. At the other end of the scale, Piercy and Lane demonstrate that heavy investment in relationships with over demanding and under achieving accounts is a costly measure that must be managed towards the direct channel – that is to say, the relationship should be managed through inexpensive channels such as the internet or call centres as opposed to costly key account management. The study garners opinion on this hypothesis from three well respected members of the pharmaceutical field and seeks to explore if this new approach will work. The initial findings were to the contrary but the possibility of using an inverse hypothesis seemed to be a viable option among the respondents. In short, the study concluded that in some cases, PharmCo should try to become strategically entrenched in order to de-commoditise their product. It was also suggested that strategic entrenchment could be seen as a viable selling option in certain markets. That is to say, a state of highly integrated relationship would be offered to a buyer who could promise a certain level of volume.